2015
DOI: 10.1180/minmag.2015.079.4.06
|View full text |Cite
|
Sign up to set email alerts
|

Khvorovite, Pb2+4Ca2[Si8B2(SiB)O28]F, a new hyalotekite-group mineral from the Darai-Pioz alkaline massif, Tajikistan: Description and crystal structure

Abstract: Khvorovite, ideally Pb42+Ca2[Si8B2(SiB)O28]F, is a new borosilicate mineral of the hyalotekite group from the Darai-Pioz alkaline massif in the upper reaches of the Darai-Pioz river, Tajikistan. Khvorovite was found in a pectolite aggregate in silexites (quartz-rich rocks). The pectolite aggregate consists mainly of pectolite, quartz and fluorite, with minor aegirine, polylithionite, turkestanite and baratovite; accessory minerals are calcite, pyrochlore-group minerals, reedmergnerite, stillwellite-(Ce), pek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Previous crystal-structure work on hyalotekite-group minerals (e.g. Sokolova et al , 2000; Pautov et al , 2015) identified two distinct tetrahedrally coordinated sites, B occupied solely by B 3+ , and T occupied by B 3+ and Si 4+ . As we shall show later, the B site in other potential hyalotekite-group minerals may be occupied by cations other than B 3+ , and hence we relabel the B and T sites as T (1) and T (2).…”
Section: The Hyalotekite-type Structurementioning
confidence: 96%
See 4 more Smart Citations
“…Previous crystal-structure work on hyalotekite-group minerals (e.g. Sokolova et al , 2000; Pautov et al , 2015) identified two distinct tetrahedrally coordinated sites, B occupied solely by B 3+ , and T occupied by B 3+ and Si 4+ . As we shall show later, the B site in other potential hyalotekite-group minerals may be occupied by cations other than B 3+ , and hence we relabel the B and T sites as T (1) and T (2).…”
Section: The Hyalotekite-type Structurementioning
confidence: 96%
“…(2000) for kapitsaite-(Y), <Si–O> = 1.617 Å, and by Pautov et al . (2015) for khvorovite, <Si–O> = 1.617 Å, indicate that the Si sites are occupied only by Si 4+ and that there is negligible substitution of B 3+ at the Si sites. The < T (1)–O > distances are 1.480 and 1.478 Å in these two minerals, the same within one standard deviation as the grand < B 3+ –O > distance of 1.476 Å reported for borate minerals by Hawthorne et al .…”
Section: Site Occupanciesmentioning
confidence: 96%
See 3 more Smart Citations